Simulation of the normal and emergency operation of interconnected power system of Ukraine for frequency stability study - Kyrylenko, O.V.; Pavlovsky, V.V.; Steliuk, А.О.; Lenga, O.V.; Vyshnevskyi, M.V. (Технічна електродинаміка, 2017)
Integration of interconnected power system (IPS) of Ukraine to the European Network Transmission System Operators for Electricity (ENTSO-E) requires an improvement of Ukrainian frequency automatic emergency control and harmonization with load-frequency control according to requirements of ENTSO-E. In order to investigate processes of frequency and active power control, it is necessary to develop the detailed simulation model including models of automatic under frequency load shedding (UFLS) relays, special protection automatics (SPA) of the nuclear power plants, automatic generation control (AGC) as well as 750-220 kV transmission networks of IPS of Ukraine. The frequency stability phenomena have been studied by time domain simulation using the detailed model realized in DIgSILENT PowerFactory software. The simulation results for different disturbances are presented. Підключення об’єднаної енергетичної системи (ОЕС) України на паралельну роботу з енергооб’єднанням ENTSO-E потребує удосконалення протиаварійного керування та гармонізації вимог щодо автоматичного регулювання частоти та потужності відповідно до тих, що діють в ENTSO-E. Для дослідження процесів зміни частоти та активної потужності необхідно розробити деталізовану модель, яка містить пристрої автоматичного частотного розвантаження, частотну автоматику енергоблоків атомних електростанцій, систему автоматичного регулювання частоти та потужності, а також магістральні мережі 750-220 кВ ОЕС України. Досліджено стійкість за частотою шляхом моделювання електромеханічних перехідних процесів з використанням програмного забезпечення DIg-SILENT PowerFactory. Наведено результати досліджень для виникнення різних збурень. Подключение объединённой энергетической системы (ОЭС) Украины на параллельную работу с энергообъединением ENTSO-E требует усовершенствования противоаварийного управления и гармонизации требований в части автоматического регулирования частоты и мощности в соответствии с действующими в ENTSO-E. Для исследования процессов регулирования частоты и активной мощности необходимо разработать детализированную модель, учитывающую устройства автоматической частотной разгрузки, частотную автоматику энергоблоков атомных электростанций, систему автоматического регулирования частоты и мощности, а также магистральные сети 750-220 кВ ОЭС Украины. Исследована устойчивость по частоте путем моделирования электромеханических переходных процессов с использованием программного обеспечения DIgSILENT PowerFactory. Приведены результаты исследований в случае возникновения различных возмущений.